Beneficial but Constrained: Role of Urban Agriculture Programs in Supporting Healthy Eating Among Youth. Issue 3 (3rd July 2017) - Raj, Subhashni; Raja, Samina; Dukes, Bree-Ana
ABSTRACT: A number of efforts to alleviate low rates of fruit and vegetable consumption among youth in the United States have emerged in recent years. This study examines how engagement in urban agriculture (UA) programming influences fruit and vegetable consumption among urban youth in Buffalo, New York. Results indicate change in some food behaviors—youth are willing to try new foods—but not others. Results suggest that fruit and vegetable consumption is associated with gender and the median household income of neighborhoods where youth live. The study demonstrates that UA programming is beneficial but not sufficient in engendering healthy eating behavior in youth.